Catalytic approaches towards highly durable proton exchange membrane fuel cells with minimized Pt use. Issue 23 (26th May 2022) - Kim, Hee-Eun; Kwon, Jaehoon; Lee, Hyunjoo
Abstract : Catalytic approaches to enhance PEMFC performances are introduced, especially focusing on the studies reporting MEA cell data. Abstract : Proton exchange membrane fuel cells (PEMFCs) produce electricity from H2 without carbon emission, and they are considered as environmentally benign energy conversion devices. Although PEMFCs are mature enough to find themselves in a few commercial automobiles such as Hyundai Nexo and Toyota Mirai, their durability should be enhanced, especially under transient conditions, and Pt use should be reduced significantly to expand their market. Herein, we introduce examples of how catalysts can contribute to enhancing the durability of PEMFCs while minimizing Pt use. Numerous electrocatalysts have been reported claiming superior activity in a half-cell setup, but they often fail to show the same enhancement in a single cell setup due to various transfer problems, impurity poisoning, etc. This perspective focuses on catalysts tested in a membrane-electrode-assembly (MEA) setup. As examples to obtain durability under transient conditions, catalysts used in reversal-tolerant anodes (RTAs) and selective anodes are explained. RTAs can endure sudden H2 starvation, and selective anodes can operate properly when O2 is unexpectedly mixed with H2 in the anode. As examples with high durability in long-term operation, Pt-based nanoparticle catalysts encapsulated with carbon shells are explained. Interestingly, PtCo nanoparticles supported on Co–N–C or PtFe nanoparticles encapsulated with a carbon shell presented a superior cell performance in spite of <1/10 Pt use in an MEA setup. Non-Pt group metal (PGM) catalysts used in an MEA setup are also briefly explained. With these highly durable catalysts which can respond properly under transient conditions with minimum Pt use, PEMFC technology can bring about a more sustainable society.